PENGARUH KONSERVATISME AKUNTANSI, LEVERAGE DAN DEFAULT RISK TERHADAP EARNINGS RESPONSE COEFFICIENT (ERC) PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2023 - Tania Apriliyani; Pujianto Pujianto; Pramandyah Fitah Kusuma (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
This study aims to determine and analyze the influence of Accounting Conservatism, Leverage, and Default Risk on the Earnings Response Coefficient (ERC). There are 95 companies as the population in this study. The sampling technique used in this research is purposive sampling, resulting in a sample of 84 companies in three periods from the food and beverage subsector. Data analysis was conducted using statistics with the aid of SPSS version 27. Based on the results of the data analysis using the t-test, it is known that partially, accounting conservatism has a significant effect on the earnings response coefficient, leverage has a significant negative effect on the earnings response coefficient, and Default Risk has a significant effect on the earnings response coefficient. Meanwhile, based on the results of the data analysis using the F test, it is known that simultaneously accounting conservatism, leverage, and default risk have an effect on the earnings response coefficient